Biodiversity of Parasitengona (Acari: Prostigmata) in the northern and southern slopes of Joghtai mountain range, Razavi Khorasan province - Tara Pourmatin; Marjan Seiedy; Masoud Hakimitabar; Najmeh Kiany (نامه انجمن حشره‌شناسی ایران)
The insects could be parasitized by a range of parasites. One of the most important parasites that attack them are Parasitengona (Acari: Prostigmata) mites. Regular sampling was done during the summer and fall seasons in the years 2021-2022 in the two northern and southern slopes of the Joghtai mountain range located in Razavi Khorasan province. The collected mite samples were separated from the short-horned grasshoppers (Orthoptera: Acrididae) and the mite samples were transferred to microtubes containing 75% alcohol and then they were cleared in Nesbitt's Fluid and mounted on a microscope slide for identification. After identifying the samples, biodiversity and species abundance were analyzed using SPSS software. The results led to the identification of three species, Eutrombidium sorbasiensis Mayoral & Barranco, 2004 ،Abalakeus lorestanicus Saboori & Lachinani ، 2003, Charletonia damavandica Karimi Irvanlou, Kamali & Talebi, 2002. Eutrombidium sorbasiensis was the most abundant species in all stations. The diversity of mites in the southern slope was significantly higher than the northern slope (p-value=0.005). Also, diversity was high in higher altitudes (p-value=0.001). Species richness was also significantly higher in the northern slope than in the southern slope (p-value=0.01) and species evenness in the southern slope was significantly higher than in the northern slope (p-value=0.001). The highest species richness and evenness were also seen in the high altitudes, and the low altitudes lacked richness and evenness.